2009
DOI: 10.1016/j.juro.2008.10.102
|View full text |Cite
|
Sign up to set email alerts
|

A Panel of Angiogenic Factors for Early Bladder Cancer Detection: Enzyme Immunoassay and Western Blot

Abstract: Quantitative measurement of urinary angiogenic factors in voided urine samples by enzyme-linked immunosorbent assay was reliable. The sensitivity of basic fibroblast growth factor and hepatocyte growth factor was superior to that of the other investigated markers and of cytology in low grade and early stage cases, suggesting their convenience as sensitive, noninvasive diagnostic and screening tools for bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…Angiogenin binds to a cell surface and these complex results in plasmin generation, which directly degrades the extracellular matrix facilitating cell migration and invasion [9]. When we compared the correlation between the positivity rate of urinary angiogenin and the different clinicopathological factors in the malignant group, Eissa et al found that angiogenin was highly expressed in patients with bladder SCC vs. bladder TCC (76% vs. 73%) [9]. In our study angiogenin was also highly expressed in SCC vs. TCC of bladder cancer (100% vs. 60.46%) with significance vale (p= 0.041).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiogenin binds to a cell surface and these complex results in plasmin generation, which directly degrades the extracellular matrix facilitating cell migration and invasion [9]. When we compared the correlation between the positivity rate of urinary angiogenin and the different clinicopathological factors in the malignant group, Eissa et al found that angiogenin was highly expressed in patients with bladder SCC vs. bladder TCC (76% vs. 73%) [9]. In our study angiogenin was also highly expressed in SCC vs. TCC of bladder cancer (100% vs. 60.46%) with significance vale (p= 0.041).…”
Section: Discussionmentioning
confidence: 99%
“…Since it may have a role in the development and evolution of carcinomas, it is a particularly interesting molecule to study as a potential tumor marker and / or prognostic indicator for urinary bladder cancer [9].…”
Section: Introductionmentioning
confidence: 99%
“…Each urine sample was centrifuged and then the urinary sediment was washed with PBS. A portion of the pellet was used for cytological and microscopic examinations (16) and the other portion was treated with protease inhibitor cocktail (8) and stored at À80 C for further processing to extract DNA to be used for detection of methylated APC and RARb 2 .…”
Section: Collection Of Samplesmentioning
confidence: 99%
“…Alternatively, urine cytology is known for its good specificity but poor sensitivity for early stages and low grades. An array of urine markers were evaluated to improve the diagnostic ability of urine cytology and, perhaps, to reduce the need for frequent cystoscopies during follow-up, especially in those with low-risk disease (4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Although uri-nary cytology is widely used for screening for bladder cancer, it is sometimes difficult to judge cytologic specimens, particularly for low-grade cancers [5]. Therefore new, noninvasive methods for bladder cancer detection would open new possibilities in diagnosis and monitoring [6], as well as in screening of groups at risk such as bilharzial infested patients [7][8][9]. An ideal test to monitor bladder cancer should be objective, noninvasive, easy to administer and interpret and have high sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%